Digitisation of traditional product using computer aided design technology: a case study on desiccant compressed air dryer. (24th April 2019) - Sunil, D.T.; Devadasan, S.R.; Vinod, M.; Natarajan, K.S.
In order to face the competition, traditional manufacturing companies are required to digitise the products by applying computer-aided design (CAD) for infusing innovative features in them. In the context of this realisation, a case study on digitising a traditional product by name 'desiccant compressed air dryer' (DCAR) by applying CAD technology which is presented in this paper was carried out. The procedures adopted to create the CAD models of six subassemblies of DCAR and its assembly by using a CAD software package namely Creo Parametric 2.0 are described. Then the advantage of digitising the traditional products using the CAD technology is described. The article is concluded by stating that utilising this kind of facilities that are available in CAD software packages will enable traditional manufacturing companies to become agile by quickly adding amazing features that will delight the customer.